3D printing properties of Flammulina velutipes polysaccharide-soy protein complex hydrogels. (December 2022) - Pan, Hongshan; Pei, Fei; Ma, Gaoxing; Ma, Ning; Zhong, Lei; Zhao, Liyan; Hu, Qiuhui
Abstract: Food 3D printing targets special consumers, such as children, elderly individuals and patients. For food 3D printing, soy protein isolate hydrogels are widely used but have obstacles in hydrogel reshaping. To improve the physical properties of the hydrogel for 3D printing, soy protein isolate can form composites with other hydrocolloids, such as Flammulina velutipes polysaccharide. Therefore, we evaluated the 3D printing accuracy and stability of the composite between soy protein isolate and Flammulina velutipes polysaccharide. The hydrogel of the composite with thermal treatment after 3D printing was accurate (>99.7%) and stable (>99.9%). Adding Flammulina velutipes polysaccharide and thermal treatment made the hydrogel less viscous and stronger, with a more uniform and denser microstructure. Thermal denaturing soy protein and introducing –OH from Flammulina velutipes polysaccharide to enhance β-sheets were the likely reasons for the improved hydrogel characteristics. Our findings suggested that adding Flammulina velutipes polysaccharide and thermal treatment could improve food 3D printing. Highlights: Flammulina velutipes polysaccharide (FVP) improved the 3D printability of soy protein. Heated FVP and soy protein isolate (h-FVP-SPI) showed high accuracy via 3D printing. More β-sheets in h-FVP-SPI leaded to increased G′ and better stability. Strong networks of h-FVP-SPI leaded to a uniform surface and low free water.